Visual Function Status in Children with Cerebral Palsy. - Vasanth, JayaRajini; Jacob, Namita; Viswanathan, Subbaiya (Optometry & Visual Performance, 2014)
Background: This study was conducted in the school for special children in and around Chennai, Tamilnadu, India. The study aimed at giving an appropriate refractive correction for the children with special needs. Methods: Three hundred and seventy-six children with cerebral palsy were assessed. Visual function and accommodative status was evaluated. Visual acuity was assessed using LEA paddles and LEA symbols depending upon the age, cooperation, and cognitive ability of the child. Visual fields were assessed by using LEA flicker wand. The Hirschberg and cover tests were done to identify strabismus. Mohindra near retinoscopy was done to find the static refractive status of the children followed by cycloplegic refraction. Accommodation was measured using a modification of MEM and Nott dynamic retinoscopy technique. The values were compared with the age-matched normal values. Results: The mean age of the children was 6.48 years. Near normal vision was observed in 12.67%, 43.66% had moderate low vision, 26.76% had severe low vision, and 16.91% had profound low vision. Strabismus was present in 43.89% of the children. Among those who had strabismus, nystagmus was present in 7.45%. The accommodative status was assessed by MEM and Nott dynamic retinoscopy. The findings were as follows: lead of accommodation 18.60%, lag of accommodation 50.27%, and normal accommodative status 31.13%. Conclusion: This study shows that most of the children with cerebral palsy have a lag of accommodation. Hence, refractive error was corrected accordingly, considering their binocular status. The importance of testing binocular and accommodative status in children with special needs cannot be understated.